Waterfalls and Rapids and their touristic potential in Vietnam - Ngọc, Nguyễn; Ngân, Sái Thị (Vietnam Journal of Earth Sciences, 2014)
Waterfalls and river rapids are the forms of natural resources which play significant role for socio-economic development and they are related to the scientific and technical fields such as Geology, Geomorphology, Geography, Hydrology, Hydro Power, Water resources, Fisheries, Natural resources and Environment and Tourism, etc. The characteristics of the territory of Vietnam are three-quarters of mountainous areas with the humid tropical monsoon climate. There are 2630 rivers by 10 km of length and over 350 waterfalls and rapids which are distributed in the territory of 38/63 provinces and cities of the country. Waterfalls and rapids are two different physical entities which are geological/geomorphological formations or simultaneously products of the processes of geology, geomorphology, topography and hydrology. They belong to natural touristic resources. On the basis of classification, there are 11 types of waterfalls and rapids in Vietnam. This natural condition is very suitable for ecological tourism development, but at present time only 15% of that potential is exploited.